Heme Degrading Protein HemS Is Involved in Oxidative Stress Response of Bartonella henselae - Liu, MaFeng (Public Library of Science, 2012)

(untitled)
Bartonellae are hemotropic bacteria, agents of emerging zoonoses. These bacteria are heme auxotroph Alphaproteobacteria which must import heme for supporting their growth, as they cannot synthesize it. Therefore, Bartonella genome encodes for a complete heme uptake system allowing the transportation of this compound across the outer membrane, the periplasm and the inner membranes. Heme has been proposed to be used as an iron source for Bartonella since these bacteria do not synthesize a complete system required for iron Fe(3+)uptake. Similarly to other bacteria which use heme as an iron source, Bartonellae must transport this compound into the cytoplasm and degrade it to allow the release of iron from the tetrapyrrole ring. For Bartonella, the gene cluster devoted to the synthesis of the complete heme uptake system also contains a gene encoding for a polypeptide that shares homologies with heme trafficking or degrading enzymes. Using complementation of an E. coli mutant strain impaired in heme degradation, we demonstrated that HemS from Bartonella henselae expressed in E. coli allows the release of iron from heme. Purified HemS from B. henselae binds heme and can degrade it in the presence of a suitable electron donor, ascorbate or NADPH-cytochrome P450 reductase. Knocking down the expression of HemS in B. henselae reduces its ability to face H(2)O(2) induced oxidative stress.